The Effect of Academic Supervision on Teacher Pedagocical Competence and Techer Performance: The Role Moderating by Teacher Efficacy - Singerin, Sarlota (International Journal of Elementary Education, 2021)
The role of a teacher is very important in the world of education. The success of the performance shown by the teacher is influenced by the surrounding environment, one of which is the role of the school principal as the school supervisor. In addition to school principal furniture, performance satisfaction and work performance are strongly influenced by the efficacy of teachers. This study aims to determine the effect of academic supervision on pedagogic competence and performance moderated by teacher efficacy. The results show that academic supervision has an effect on pedagogical competence with a statistical T score greater than T table (4.790> 1.984) and a P value of 0.000 or smaller than the 5% alpha standard (0.000 <0.05), academic supervision has an effect on teacher performance with a statistical T value greater than the T table (4.344> 1.984) and a P value of 0.000 or less than the 5% alpha standard (0.000 < 0.05), Efficacy is not able to moderate the effect of academic supervision on pedagogic competence with a statistical T value score smaller than the T table (0.946 <1.984) and a P value of 0.345 or greater than the 5% alpha standard (0.345> 0.05). Self-efficacy is able to moderate the effect of academic supervision on teacher performance with a statistical T value greater than T table (3.165> 1.984) and a P value of 0.002 or less than the 5% alpha standard (0.032 <0.05). Testing the moderation effect shows that Efficacy is able to moderate the effect of supervision on Teacher Performance, while on Pedagogic Competence it shows Efficacy has not been able to provide a significant moderating effect on Pedagogic Competence